Methodological characteristics of studying Commitment to the practice of physical activity and exercise in the general population: a systematic review - Zapata Lamana, Rafael (2021)
Although the literature on sports commitment within the sports population is extensive, in-depth studies of the commitment to the practice of physical activity and exercise in the general population are needed. The aim of this paper was to synthesize the methodological characteristics of articles that have studied the commitment to the practice of physical activity and exercise in the general population. A systematic review was developed following the PRISMA statement. Furthermore, electronic searches were conducted in the PsycINFO and Medline databases from 2009 to 2019. A total of 14 articles was selected, mainly with cross-sectional designs. The most studied population included female university students with no clinical condition. All instruments used to assess commitment to physical activity and exercise were written in English, mostly applied in the United States, and used a Likert scale with high reliability. The main variables associated with the evaluation of commitment were age, gender, ethnic origin, educational and economic level, level of physical activity, behavior, eating disorders, and body mass index, as well as sociocognitive variables such as self-efficacy, social support, and perceived barriers and benefits of physical activity. This review provides a profile of the population in which the commitment to physical activity and exercise is evaluated, the instruments used, and associated variables, which updates the existing knowledge about the commitment to physical activity and exercise in the general population.